Alpha-Glucosidase Inhibition and Hypoglycemic Activities of Sweitenia mahagoni Seed Extract - TUTIK WRESDIYATI; SITI SA’DIAH; ADI WINARTO; VENNY FEBRIYANI (Bogor Agricultural University, Indonesia, 2015)
Inhibition of α-glucosidase and hypoglycemic activity are two effects commonly used to identify bioactive compounds with potential to treat diabetes. The objectives of this study were to analyse and compare the bioactive compounds and α-glucosidase inhibitory effect of four different types of Swietenia mahagoni seed extract, and to analyse the hypoglycemic activity of the greatest inhibition of α-glucosidase-extract in rats. The extracts were obtained using two different solvents (aqueous and ethanol) and two different methods: maceration and reflux methods. This resulted in four types of extract varying by solvent and extraction method. Testing of these extracts for α-glucosidase inhibitory effect was carried out in vitro using spectrophotometer. Testing for hypoglycemic activity was carried out in vivo using rats. A total of 40 male Sprague-Dawley rats were divided into eight groups: (1) the negative control group, received an oral dose of aquadest only, (2) the positive control group, was given 90% sucrose orally without S. mahagoni seed extract, and five treated groups (3-7), were given 90% sucrose followed by the best extract-ethanolic S. mahagoni seed extract in doses of 100, 200, 300, 400, and 500 mg/kgBW, and (8) the acarbose group, was given 90% sucrose orally followed by acarbose. Glucose levels in each animal were measured at 0, 30, 60, 90, and 120 min after treatment. The results showed the greatest inhibition of α-glucosidase in ethanolic extract, using maceration methods. This ethanolic-maceration S. mahagoni seed extract also showed hypoglycemic effects in hyperglycemic rats at dose from 100 to 500 mg/kgBW. Ethanolic extract of S. mahagoni seed, using maceration method, can be proposed as potential antidiabetic agent.